APLASTIC ANEMIA ET CAUSA OF SUSPECT VIRAL HEPATITIS INFECTION: A CASE REPORT - I Wayan Wawan Lismana (Universitas Udayana, 2014)
Aplastic anemia is anemia that occurs because of a failure of hematopoiesis is relatively rarebut can be life threatening. The cause of aplastic anemia itself is still largely unknown oridiopathic. Minority of cases mainly due to a virus infection, one of which is viral hepatitishas long been known to cause symptoms of aplastic anemia. This report discusses thesuspected aplastic anemia caused by hepatitis virus infection. Course of the disease or theprognosis of aplastic anemia varies, but a poor prognosis may occur if not handled with goodtreatment